1993
DOI: 10.3109/02713689309020398
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of the gene for lens major intrinsic protein in the CAT mouse

Abstract: Immunocytochemistry fails to detect expression of the lens major intrinsic protein (MIP) in 16-day embryos of the congenitally cataractous mouse, CAT, which inherits a dominant mutation assigned to the distal end of mouse chromosome 10. In situ hybridisation, however, detects MIP mRNA in CAT embryo lens fibre cells at a level approximating 60% of that detected in embryonic lens fibres of the non-cataractous MF1 mouse. Northern blot hybridisation reveals that the most abundant MIP mRNA transcript in the adult C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Human AQP1 and AQP2 natural mutations resulted in recessive traits (Deen et al, 1994Preston et al, 1994) whereas all of the thus far documented AQP0 mutations in human (Berry et al, 2000;Francis et al, 2000a,b;Geyer et al, 2006) and mice (Shiels and Griffin, 1993;Shiels and Bassnett, 1996;Shiels et al, 2000;Okamura et al, 2003) led to dominant lens cataract. Mutations in structural proteins cause dominant inherited traits (Francis et al, 2000a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Human AQP1 and AQP2 natural mutations resulted in recessive traits (Deen et al, 1994Preston et al, 1994) whereas all of the thus far documented AQP0 mutations in human (Berry et al, 2000;Francis et al, 2000a,b;Geyer et al, 2006) and mice (Shiels and Griffin, 1993;Shiels and Bassnett, 1996;Shiels et al, 2000;Okamura et al, 2003) led to dominant lens cataract. Mutations in structural proteins cause dominant inherited traits (Francis et al, 2000a,b).…”
Section: Discussionmentioning
confidence: 99%
“…AQP 0/MIP28 was isolated from lens epithelium. Absence of normal AQP 0 protein is linked to cataract formation in mutant mice (Shiels & Griffin 1993). AQP 1/channel forming integral membrane protein (CHIP)-28 is the most ubiquitous of the AQP family and is expressed in a number of organs and tissues (Echvarria et al, 1994;Heymann et al, 1998;Yang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mip forms specialized junctions between the fiber cells and can be first detected in the primary fiber cells of the early lens vesicle. In situ hybridization demonstrated that Mip expression is highest in the elongating fiber cells in the bow region of the lens; Mip antiserum specifically decorates fiber cell membranes, highlighting their regular anterior to posterior organization (Shiels and Griffin, 1993;Zhou et al, 2002). Mip is also referred to aquaporin; a recent review was published by Agre and Kozono (2003) …”
Section: Aquaporin/mipmentioning
confidence: 99%
“…Sequence analysis revealed that the Cat Fr mutation is due to a transposon-induced splicing error leading to a truncated form of Mip transcripts. However, the mutation in the Cat Lop leads to a single amino-acid substitution, which inhibits targeting of Mip to the cell membrane (Shiels and Griffin, 1993;Shiels and Bassnett, 1996). Recently, a new mutant allele (Cat Tohm ) was reported, which is characterized by a 12 bp deletion and a corresponding loss of 4 amino acids within the second transmembrane region (Okamura et al, 2003).…”
Section: Aquaporin/mipmentioning
confidence: 99%